STUDY LITERATURE REVIEW DENGAN PUBLISH OR PERISH: IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI TERHADAP KETERAMPILAN PROSES SAINS SISWA SD - Wardani, Ririn Pertiwi Rindang Rahma; Suryanti; Sudibyo, Elok (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to investigate literature studies using the Publish or Perish method: Implementation of the Inquiry Learning Model on Elementary School Students' Science Process Skills. The research method used is a systematic literature review (Systematic Literature Review or SLR) using the Publish or Perish 8 application and utilizing the Google Scholar and Crossref databases. Inclusion criteria involved journal articles published between 2020 and 2024. The identification stage in Google Scholar produced 85 articles, while in Crossref found 12 articles. After the filtering stage, 36 relevant articles were selected, while the other 51 articles were deemed irrelevant. At the feasibility stage, there were 11 articles that were deemed worthy, and 25 articles that were not. At the final stage of inclusion, only 6 articles met the criteria and were accepted for further analysis. The results obtained were that most of the methods used were experimental, the samples were class IV and V elementary school. The various inquiry models used are the guided inquiry model, guided and expository inquiry, process-oriented guided inquiry using LKS supplements, inquiry learning model assisted by PhET media, and guided inquiry using LKS.